Democratic Education for an Active Citizenship - Antonio Bolívar (Universidad Autónoma de Madrid, 2016)
Democratic education has a double meaning: educating for democracy by exercising democracy, it is -at the same time- a goal and context of education. Public education should train future citizens to actively participating in the public sphere, without risk of exclusion. This includes ensuring that all people acquire virtues, values and skills required in order to become participating citizens, and to insert socially. The article is an analysis and current review of what active citizenship and its construction means both in teaching and in the organizational culture of the school. Finally, it is emphasized that it is a matter to build local and social community.